2019
DOI: 10.4187/respcare.06206
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Home Oxygen Therapy on the Level of Physical Activities in Daily Life in Subjects With COPD

Abstract: BACKGROUND: Chronic hypoxemia in patients with COPD is a limiting factor that is associated with disease progression and significantly contributes to decreased physical activity. Although correction of hypoxemia results in physiological improvements, oxygen therapy may be related to social isolation and inactivity. However, few studies have objectively investigated the level of physical activity in daily life (PADL) in these patients. The objective of this study was to compare the level of PADL in subjects wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 43 publications
0
12
0
10
Order By: Relevance
“…Using the same device, a multi-center study conducted on more than 1000 COPD patients33 reported that age, BMI, dyspnea severity and airflow obstruction were associated with PA measures and hourly patterns. In a recent smaller study,20 patients on LTOT showed less time walking, as well as in physical activities, in physical activities ≥ 3 METs, and in physical activities < 1.5 METs, and took fewer steps compared to control patients not needing LTOT. Physical inactivity was present in 83% of LTOT subjects and 60% of control subjects.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Using the same device, a multi-center study conducted on more than 1000 COPD patients33 reported that age, BMI, dyspnea severity and airflow obstruction were associated with PA measures and hourly patterns. In a recent smaller study,20 patients on LTOT showed less time walking, as well as in physical activities, in physical activities ≥ 3 METs, and in physical activities < 1.5 METs, and took fewer steps compared to control patients not needing LTOT. Physical inactivity was present in 83% of LTOT subjects and 60% of control subjects.…”
Section: Discussionmentioning
confidence: 89%
“…Although correction of hypoxemia results in physiological improvements, LTOT may be related to social isolation and inactivity due to clinical, physiological and organizational problems. Despite reports that pulmonary rehabilitation can improve exercise capacity also in these patients,16 there are few studies evaluating PA in COPD patients on LTOT 1720. Furthermore, to the best of our knowledge, there is no information on the influence of exercise-induced desaturation on PA or on the burden of oxygen-delivery devices.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have evaluated the sedentary time of patients on LTOT [9,43], and the sedentary time of Japanese patients on LTOT has not been clarified. The sedentary time of patients on LTOT has been reported to be 623 min [9]. This finding is consistent with the sedentary time of the patients enrolled in this study at 600 min.…”
Section: Characteristics Of Sedentary Time In Patients On Ltotmentioning
confidence: 99%
“…In a meta-synthesis of qualitative research studies, Cullen et al [46] noted that LTOT equipment usage leads to incapacity because of psychological factors such as stigma and prejudice. Furthermore, Cani et al [9] showed that the length of the cannula from the concentrator decreased mobility in patients on LTOT. Based on the findings of previous studies, the activity of patients on LTOT may be hindered by LTOT equipment.…”
Section: Characteristics Of Sedentary Time In Patients On Ltotmentioning
confidence: 99%
See 1 more Smart Citation